2021
DOI: 10.1371/journal.pone.0247140
|View full text |Cite
|
Sign up to set email alerts
|

Low muscle mass assessed by psoas muscle area is associated with clinical adverse events in elderly patients with heart failure

Abstract: Background Acute decompensated heart failure (ADHF) is a growing healthcare burden with increasing prevalence and comorbidities due to progressive aging society. Accumulating evidence suggest that low skeletal muscle mass has a negative impact on clinical outcome in elderly adult population. We sought to determine the significance of psoas muscle area as a novel index of low skeletal muscle mass in elderly patients with ADHF. Methods In this single-center retrospective observational study, we reviewed consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…Loss of skeletal muscle mass and function is an important manifestation of aging. Age-related skeletal muscle disorder involving the accelerated loss of muscle mass and function is associated with falls, frailty, and mortality [ 2 , 3 ]. Studies have shown that insulin resistance, inflammation, denervation, and autophagy can cause skeletal muscle disorder [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of skeletal muscle mass and function is an important manifestation of aging. Age-related skeletal muscle disorder involving the accelerated loss of muscle mass and function is associated with falls, frailty, and mortality [ 2 , 3 ]. Studies have shown that insulin resistance, inflammation, denervation, and autophagy can cause skeletal muscle disorder [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the primary hip flexor and a stabilizer of the lumbar spine and sacroiliac joint, the psoas muscle is essential for walking, raising from a seated position, and maintaining balance. The specific association of sarcopenia with PMA has been described in previous studies 10,12 and may be a practical method to screen patients at risk before initiating treatment. For example, autosegmentation software can rapidly analyze a large number of scans and may even obviate the need for manual measurement, allowing for an automated work flow that requires only occasional review for quality assessment purposes 13 .…”
mentioning
confidence: 89%
“…Estimates of lean muscle mass were based on a cross-sectional area of all skeletal muscle (skeletal muscle area) as well as the paired psoas muscles (psoas muscle area [PMA]), both of which have been used as surrogates for total lean muscle mass in a number of studies. 7,9,10 In a multivariate analysis of OS, they found that age, comorbidities, PMA, and baseline prostatespecific antigen were associated with overall mortality. These variables were fed as inputs for a recursive partitioning analysis using the RTOG 0126 cohort as the training set, which generated four prognostic groups primarily based on comorbidities in patients younger than age 70 years, and significantly, psoas area in patients aged 70 years and older.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the baseline characteristics of the overall study subjects, and the characteristics of the patients in the development and validation groups. Among the included patients, 366 (63%) were male, the average age was 69 years (12), and the dialysis history was 13 years (11). Of the 619 patients, 226 (37%) were diagnosed with low muscle mass.…”
Section: Study Populationmentioning
confidence: 99%